PEDIATRIC RETINAL DETACHMENT IN AN ASIAN POPULATION WITH HIGH PREVALENCE OF MYOPIA: Clinical Characteristics, Surgical Outcomes, and Prognostic Factors. Issue 9 (September 2019) - Tsai, Andrew S. H.; Wong, Chee Wai; Lim, Laurence; Yeo, Ian; Wong, Doric; Wong, Edmund; Ang, Chong Lye; Ong, Sze Guan; Lee, Shu Yen; Tan, Gavin
Abstract : Purpose: To evaluate the clinical characteristics and surgical outcomes of pediatric retinal detachments (RDs) in an Asian population. Methods: Retrospective review of 171 eyes of 152 pediatric patients with rhegmatogenous RD over a 20-year period. Results: Myopia was the most common risk factor in our population. At 6 months, primary anatomical success was 60.7%, and overall anatomical success was 86.7%. A total of 46.8% had best-corrected visual acuity of 20/40 or better, and 81.6% had best-corrected visual acuity of 20/200 or better. In primary RDs, high myopia (⩽−6D) patients had a lower primary anatomical success compared to patients with moderate myopia (⩽−2D) (59.3 vs. 100% P = 0.03). Increasing age and absence of proliferative vitreoretinopathy were associated with anatomical and visual success. Pars plana vitrectomy as the primary procedure was associated with decreased odds of anatomical success. A longer duration of symptoms, cataract, and a larger RD extent were associated with poorer functional outcome. Conclusion: Myopia was the commonest risk factor for pediatric RD in our population. Good anatomical and functional outcome can be achieved with surgery. Increasing age at presentation and absence of proliferative vitreoretinopathy was associated with anatomical and functional success. High myopia was associated with poorer anatomical and functional outcome. Abstract : Myopia was the commonest risk factor for pediatric retinal detachment in this Asian population. Increasing age and absence of proliferative vitreoretinopathy were associated with anatomical and visual success. Highly myopic patients had poorer outcome.